Folklore and mythological foundations of Marko Cheremshyna’s artistic thinking - Maftyn, Natalia (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2023)
In the proposed scientific article the genesis of Marko Cheremshyna's artistic thinking and especially the effect and manifestations of his folklore and mythological principles on his literary texts poetic levels have been researched. Taking into consideration the writer's worldview peculiarities, the novels of the cycle "The Village During the War", "Parasochka", "Grushka", "Let them go!", "Swear off to drink copper vodka..." have been analysed. The research methodology involved the use of historical – cultural and systemic methods, mythopoetic and techniques of receptive aesthetics and elements of the theory of intertextuality. The study of Marko Cheremshyna's short stories from the chosen angle of view showed the rootedness of his artistic thinking into the deep layers of the folk worldview and the folklore imagery that reach the archetypal basis. The lyrical dominance of the writer's prose and its stylistic component in particular also emerged from the folklore and from skillful transformations of rhythm, poetic syntax of folk songs, lamentations, carols and the parallelism of their construction. The original Hutsul folklore with its relict beliefs elements, ciphers, symbols, ornamental decorations and transubstantiation of all manifestations and forms of life and lexical richness served as a model of Marko Cheremshyna’s artistic worldview, which organically combined components of realism, impressionism and non-romanticism. In Cheremshyna's object-subject model of the world, the invincible spirit of life, which corresponds to moral and ethical principles and folklore ideas about the Hutsuls' worldview takes a prominent place.